PCR TESTING FOR SARS-COV-2: PRACTICE, RECCOMMENDATIONS AND DILEMMAS - Popadic, Dusan (HEALTH CARE, 2020)
In the Covid-19 pandemic, diagnostic laboratories have met multiple new demands, which havegone beyond the existing personnel, technical and material capacities. According to the currentrecommendations, the base of laboratory diagnostics for Covid-19 is a Real-Time Reverse TranscriptionPolymerase Chain Reaction (rtRT-PCR) test, which detects the presence of SARS-CoV-2 genome in thebiological material collected from the patient. The procedure of testing can conditionally be divided intoseveral stages: 1) setting the indications for testing; 2) collecting the clinical samples and filling in thedocumentation; 3) transport of the material to the diagnostic laboratory; 4) reception and classificationof the material; 5) the analysis of samples after the reception – the preparation for rtRT-PCR; 6)rtRT-PCR; 7) communicating results. It is clear that medical microbiological services have not beenstandardized for the fight against the pandemic or great epidemics. The most efficient way to overcomesuch a situation is to define teams, which would take part in the diagnostics, when the epidemiologicalsituation demanded it. It is necessary to strive to have the unified equipment on the whole territoryof The Republic of Serbia, because in that way the maintenance and procurement of spare parts andconsumables are made easier, and the purchasing price could possibly be lowered. Reagents for theextraction and specific reagents for rtRT-PCR (primers and probes) should be standardized and madein Serbia in order to decrease the dependence on imports and make significant money savings. Thedatabase of laboratory results should be improved and organized according to the FAIR (findability,accessibility, interoperability, and reusability) principles in order to use the possibility of makingconclusions maximally.
Keywords: Covid-19, rtRT-PCR, expert’s recommendations